Implementation Of The Data Literacy Course In Supporting The OBE-Based Curriculum At Telkom University - Farhan Iswana Putra Ramadhan (EduGrows: Education and Learning Review, 2025)
This research investigates the implementation of data literacy as a compulsory course at Telkom University, aimed at supporting the professional competencies required in students' disciplines, consistent with the goals of an Outcome-Based Education (OBE) curriculum. A qualitative research method with a case study approach was utilized. The findings indicate that the implementation of the data literacy course to support the OBE curriculum at Telkom University is systematically conducted through the Plan-Do-Check-Act (PDCA) cycle. Each phase, encompassing planning, execution, and evaluation, adheres to the core principles of OBE (Design Down, Clarity of Focus, Expanded Opportunity, High Expectation) and features an adaptive, achievement-oriented pedagogical approach. The successful implementation is underpinned by robust collaboration among faculty, academic units, and external stakeholders, complemented by the application of diverse teaching methods and media customized to the specific needs and characteristics of students and their fields of study.